Supporting STEM Success: Digital Curriculum Innovations to Foster Student Retention (International Journal of Scientific Research and Management (IJSRM), 2023)
STEM (Science, Technology, Engineering, and Mathematics) education is fundamental to cultivating the skills needed in today’s technologically driven world. However, STEM programs face significant challenges with student retention, particularly due to rigorous coursework, lack of support, and insufficient engagement strategies. This paper examines the role of digital curriculum innovations—such as virtual labs, adaptive learning systems, gamification, and AI-driven tutoring—in improving retention rates in STEM education. By analyzing recent studies, case examples, and student feedback, the paper reveals that these digital tools can address key retention barriers by personalizing learning experiences, enhancing engagement, and providing flexible access to educational resources. This study offers actionable insights for educators, policy makers, and institutions seeking to support student success and foster a sustainable STEM workforce through technology-enhanced curricula.